Analisis Permainan Dua Tingkat Terhadap Kebijakan Mekanisme Pembangunan Bersih (CDM) China dalam Mewujudkan Target Net-Zero Tahun 2060 - Abyan Baihaqi; Puguh Santoso; Ichsan Malik; Pujo Widodo; Achmed Sukendro (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
Originating from the redefinition of the Human Security approach as an alternative in mapping threats from individuals to social systems, such as climate change, a consciousness has emerged regarding the importance of climate balance for survival. This has also made it a global priority to focus attention on these issues. The objective of this research is to examine the dynamics of establishing China's Clean Development Mechanism (CDM) Policy as an implementation of the Paris Agreement commitment and the continuation of the Kyoto Protocol. The Two-Level Games theory introduced by Robert Putnam serves as the primary theoretical framework for this study. The research findings indicate that to achieve a win-set for CDM at the international level, strengthening diplomatic relations with the European Union is crucial, as a replacement for the leadership vacuum in the environmental regime following the United States' withdrawal. At the domestic level, the CDM win-set emphasizes the importance of support from coalitions and state institutions to provide a foundation for success. Ultimately, it becomes imperative to maximize the diplomatic process not only at the international level but also encompassing the domestic level, thereby enabling the comprehensive realization of "China's 2060 Net-Zero Goal".